The price puzzle revisited: can the cost channel explain a rise in inflation after a monetary policy shock? - Steffen Henzel; Oliver Hülsewig; Eric Mayer; Timo Wollmershäuser (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper explores whether the cost channel solves the price puzzle. We set-up a New Keynesian DSGE model and estimate it for the euro area by adopting a minimum distance approach. Our findings suggest that - under certain parameter restrictions which are not rejected by the data - the cost channel helps to generate an initial rise of inflation after a monetary contraction.
Keywords: C51; E31; E32; 330; Transmissionsmechanismus; Inflation; Geldpolitik; Schock; Ungleichgewichtstheorie; Theorie; Schätzung; EU-Staaten